Relevansi Peran Gender dan Kontribusi Ekonomi Perempuan untuk Mencapai Falah dalam Rumah Tangga - Melis Melis (An Nisa'a, 2017)
Talking about economic actors, it can be said that everyone will do economic activities. Nothing limitations on men and women, all doing economic activity. But not in all economic sectors women and men experience equality, both in opportunity and outcome of development. There is always and there is a gap in it. Just as there is in an economic household there will always be a gender gap. But the end of economic activity undertaken by economic households is to achieve prosperity or falah. Based on this it will be seen that there is a relationship or relevance between gender and also economic contribution in terms of reaching falah for household economic.